Chemical and in vitro cytotoxicity evaluation of essential oil from Eucalyptus citriodora fruits growing in the Northwestern Himalaya, India. (7th December 2015) - Koundal, Rajkesh; Kumar, Dharmesh; Walia, Mayanka; Kumar, Ashish; Thakur, Soni; Chand, Gopi; Padwad, Yogendra S.; Agnihotri, Vijai K.
Abstract: Eucalyptus citriodora is a well‐known source of essential oil. Essential oil from the fruit's of E . citriodora was extracted using the hydrodistillation method with the help of a Clevenger‐type apparatus (yield 0.23%). The phytochemicals composition of the oil was evaluated using gas chromatography (GC), GC/ mass spectrometry (MS) and nuclear magnetic resonance (NMR) techniques. The essential oil was found to be a complex mixture of mono‐ and sesquiterpenoids. The major chemical constituents identified were α ‐pinene (54.1 g/100 g), γ‐terpinene (8.6 g/100 g), E ‐caryophyllene (6.6 g/100 g), β‐pinene (6.3 g/100 g), limonene (5.5 g/100 g) and 1, 8‐cineole (4.3 g/100 g). In vitro cytotoxicity of the essential oil was evaluated using the sulphorhodamine B (SRB) assay against human lung carcinoma (A549), human epithelial cervix carcinoma (HeLa) and Chinese hamster ovarian carcinoma (CHOK1) cells. The IC50 values of the E . citriodora fruits essential oil against A549, HeLa and CHOK1 cells ranged from 87.5 to 96.8 µg/ml. The toxicity of the isolated essential oil was also assessed against human lymphocytes using the [3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide] (MTT) assay. Essential oil possesses significant cytotoxic activity. The aim of the present study was to search the Northwestern Himalaya for the new potent source of toxicologically safe essential oils. This is a first report on the chemical composition and cytotoxicity of essential oil extracted from the fruit's of E . citriodora . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Essential oil from the fruit's of Eucalyptus citriodora was evaluated for the first time using for its phytochemicals composition and activity. Major chemical constituents were observed as α‐pinene (54.1%), γ‐terpinene (8.6%), E ‐caryophyllene (6.6%), β‐pinene (6.3%), limonene (5.5%) and 1, 8‐cineole (4.3%). The IC50 of this oil against A549, HeLa and CHOK1 carcinoma cells were observed as 87.5, 92.6 and 96.8 µg/ml respectively. The toxicity of essential oil was also assessed against human lymphocytes by MTT assay.